Dances of Moors and Christians: history, legend and practice in three contemporary performances in Portugal, Spain and Brazil (Antropolítica - Revista Contemporânea de Antropologia, 2013)
Performances of dramatized encounters between “Moors” and “Christians” can be found in many European countries, with particular emphasis on Portugal and Spain, as well as in many countries of Latin and South America, where they are important elements in local patron- saint festivals and other religious celebrations. These encounters consist of choreographed sequences of varying complexity, duration and content, which in some instances are referred to as dances (see: AMADO, 1966; ALGE, 2010; RAPOSO 1998; CARRASCO URGOITI, 1996; HARRIS, 2000). I focus on three of these dramatizations, incorporated in contemporary performances in northern Portugal Sobrado town, in southern Spain Beneixama village and in the city of Pirenópolis in Brazil, respectively. Although the three performances are quite different in composition and context, they are comparable at the level of their underlying theme: the dramatized enactment of a “battle” between “Moors” and “Christians”. The article opens with a historical account of the form and content of “dances of Moors and Christians” in the European context, and how these dances have been defined and interpreted by different researchers, followed by performances descriptions in the three celebrations mentioned above, with particular regard to their relation with dance. The article concludes with a brief analysis of the role these performances played in the local community in terms of sociability and social status. The data presented is based on participant observation and interviews, carried out during fieldwork on the performances between 2008 and 2011, and combined with the analysis of secondary documentary information.